KESALAHAN EJAAN DALAM PENULISAN ARTIKEL WEB IAIN SURAKARTA DAN IMPLIKASINYA PADA PEMBELAJARAN BAHASA INDONESIA KURIKULUM 2013 DI SMP - Khotijah, Siti; Ismail, Bagus (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
The article is a written media that is used for information dissemination tools to the general public which are written based on the rules of the standard language, good and correct based on the applicable rules. This study analyzes the inaccuracy of spelling language in writing articles on the Surakarta IAIN Web as well as the implications in 2013 curriculum learning. The focus of discussion in this study is how the form of language errors in spelling in the article on Surakarta IAIN Web and the implications in 2013 curriculum learning. This is a description of the inaccuracy of spelling language in writing articles on the Surakarta IAIN Web and the implementation of learning based on the 2013 curriculum. The type of research used is descriptive qualitative. The method used is observation and documentation. Based on the results of the analysis of language errors in writing articles on the Surakarta IAIN Web, it was found that a form of error (1) the form of spelling errors included (a) a form of error in using standard language, (b) conjunctions, (d) repeated words and (e) the use of punctuation; and (2) Implementation of the 2013 curriculum in Learning includes activities (a) identifying text deficiencies based on applicable KD, (b) reviewing and revising texts based on applicable KD. The high school education unit includes text editing activities based on applicable KD.